PENERAPAN PEMBELAJARAN QUICK ON THE DRAW UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SUB POKOK BAHASAN ARITMETIKA SOSIAL SISWA KELAS VII F SEMESTER GANJIL SMP NEGERI 10 JEMBER TAHUN AJARAN 2012/2013 - Lestiyaningsih, Herdika; Hobri, H; Kristiani, Arika Indah (KadikmA, 2013)
Abstract.The objectives of this action research are to know how the implementation of learning Quick on the Draw, the students activities in learning process, and the studentâs outcomes after using the implementationof learning Quick on the Draw of Social Arithmetic at VII grade material. This implementation was conducted in two cycles, and each cycle was ending with a test. This research using Hopkins scheme model that consist of 4 phases include planning, action, observation and reflection. The object of this research was students of class VII F of SMP Negeri 10 Jember. The data collection methods of this research were observation, interview, test and documentation. In Cycle I, the research shows that studentâs activities were 85,55% and the students learning outcome were 82,85%. In Cycle II the studentâs activities were 91,42% and the students learning outcome were 97,14%. It conclude that this research can improve the studentâs learning outcome. Key Words:implementation, learningQuickon theDraw, student learning outcomes, social arithmetic